Correction: Betel quid use is associated with anemia among both men and women in Matlab, Bangladesh. - Kristin K Sznajder; Mary K Shenk; Nurul Alam; Rubhana Raqib; Anjan Kumar; Farjana Haque; Tami Blumenfield; Siobhán M Mattison; Katherine Wander (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0001677.].